Analisis Pengaruh Kinerja BPRS dan Kondisi Makroekonomi terhadap Penyaluran Pembiayaan Modal Kerja dan Investasi BPRS di Indonesia (Periode: 2011-2015) - Arno Nugroho; Muhammad Findi Alexandi; . Widyastutik (AL-MUZARA'AH, 2017)
Sharia banking operational activities to encourage the real sector is to provide financing. The Islamic Rural Bank (IRB) conducts financing for working capital and investment as it can increase economic growth in Indonesia. The purpose of this study is to analyze and compare the effect of performance IRB and macroeconomic conditions on the distribution of IRB working capital and investment financing in Indonesia from 2011 to 2015 using Vector Error Correction Model (VECM) research method with monthly data from 2011 to 2015. From the results of VECM estimates, it will be seen the response of working capital and investment financing to shocks arising from the performance IRB and macroeconomic conditions and also the contribution of each of each variable used in the study. The results of this study indicate that the effect of performance IRB and macroeconomic conditions on the working capital financing of IRB in Indonesia, have positive and significant effect on DPK, FDR, ERDPK, inflation and IPI variables have negative and significant effect on ROA, NPF, BOPO, and BI rate, and no significant effect on CAR and ERP variables. The financing of BPRS investment in Indonesia, which has positive and significant effect on the DPK, CAR, ROA, FDR, BI rate, and IPI variables, has a negative and significant effect on NPF, BOPO, ERP, ERDPK, and inflation variables.